2022
DOI: 10.1155/2022/7355485
|View full text |Cite|
|
Sign up to set email alerts
|

The Inflammasome NLRC4 Protects against Cryptococcus gattii by Inducing the Classic Caspase-1 to Activate the Pyroptosis Signal

Abstract: Cryptococcus is one of the most pathogenic invasive fungi, and its interaction with the host’s natural immunity, especially the role of the inflammasome family, has not been fully elucidated. As an important member of the inflammasome family, NOD-like receptor (NLR) family caspase recruitment domain (CARD) containing 4 (NLRC4) has been proven to protect lungs from damage from a variety of pathogens. In this study, we investigated the protective effect and mechanism of NLRC4 on cryptococcal pulmonary infection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…In this sense, some analyses were carried out with regard to autophagy markers during an infection caused by C. neoformans and it was noted that unlike in other pathogenic yeast species, cryptococcosis caused by the selective intracellular pathogen C. neoformans is less severe in the absence of autophagy [239]. Furthermore, NLRC4 inflammasome-mediated activation of caspase-1 during C. gattii cryptococcosis increases pyroptosis in phagocytes and affects their phagocytic capacity by inhibiting the yeast intracellular parasitism [240]. Ueno and colleagues even describe that C. gattii has a greater resistance to oxidative stress generated by the antifungal activity of neutrophils than C. neoformans [241].…”
Section: Cell Response Against the Infectionmentioning
confidence: 99%
“…In this sense, some analyses were carried out with regard to autophagy markers during an infection caused by C. neoformans and it was noted that unlike in other pathogenic yeast species, cryptococcosis caused by the selective intracellular pathogen C. neoformans is less severe in the absence of autophagy [239]. Furthermore, NLRC4 inflammasome-mediated activation of caspase-1 during C. gattii cryptococcosis increases pyroptosis in phagocytes and affects their phagocytic capacity by inhibiting the yeast intracellular parasitism [240]. Ueno and colleagues even describe that C. gattii has a greater resistance to oxidative stress generated by the antifungal activity of neutrophils than C. neoformans [241].…”
Section: Cell Response Against the Infectionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%